Life span and fecundity of Aiolopus thalassinus exposed to dietary heavy metals (Hg, Cd, Pb) (Bollettino di zoologia agraria e bachicoltura, 2024)
Aialapus thalassinus (Fabr. 1781) (Orthopteroidea, Caelifera Acrididae)from Kenya was reared and fed with wheat seedlings grown in water contaminatedby different heavy metal salts. Additionally, the egg-laying substrate wascontaminated.The effects of dietary heavy metals (Hg, Cd, Pb) on the life span and fecundityof A. thalassinus were studied. The life span of A. thalassinus kept on Hg, Cdand Pb contaminated food was shorter than that of control grasshoppers, whereHg showed the highest effect, followed by Pb and Cd. Females exposed to Hgand Pb had significantly shorter life spans than those exposed to Cd. Differencesin the life span between the female and male within the same exposure was significantonly during exposure to cadmium. The accumulation to Hg was propotionalto the life span in both sexes, as it increased steadily with the age. The concentrationfactors were in the order Hg > Cd > Pb. Cadmium accumulation in bothsexes increased during the maturing phase (first 8-10 days of adult stage), but itdecreased steadily when the individuals became older. Decontamination of Cdwas faster and greater in males than in females. Bioaccumulation of Pb in thegrasshoppers was significantly lower than in food.Dietary Hg reduced the fecundity, whereas females exposed to Cd laid more eggsand egg pods than in control. The effect of dietary Pb was not as negative as thatof Hg. The females during Hg exposure required 4.21 days for one oviposition,on the average, whereas those exposed to Cd and Pb contaminated food ovipositedin shorter intervals, 3.17 and 3.26 days. respectively. A higher number ofegg pods was deposited in substrates containing higher concentrations of metalsalts. Higher number of eggs per female per day and more frequent ovipositionwere accompanied by decreasing Cd concentration in the female. The life spanof such individuals were longer than those exposed to Hg and Pb.
Keywords: Aiolopus thalassinus; life span; fecundity; dietary heavy metals; Hg; Cd; Pb; oviposition